Red Blood Cell Distribution Width Predicts Mortality in Hospitalized Patients with Severe Fever with Thrombocytopenia Syndrome - Zhang S; Zhang Q; Wang J; Pan Y; Zhang Z; Geng Y; Jia B; Tian B; Xiong Y; Yan X; Li J; Wang H; et al. (Dove Medical Press, 2024)
Shaoqiu Zhang,1,* Qun Zhang,2,* Jian Wang,1,3,* Yifan Pan,4 Zhiyi Zhang,5 Yu Geng,1 Bei Jia,1 Bing Tian,2 Yali Xiong,1 Xiaomin Yan,1 Jie Li,1,3- 5 Huali Wang,6 Rui Huang,1,3- 5 Chao Wu1,3- 5 1Department of Infectious Diseases, Nanjing Drum Tower Hospital, Affiliated Hospital of Medical School, Nanjing University, Nanjing, Jiangsu, People's Republic of China; 2Department of Infectious Diseases, Affiliated Zhongda Hospital of Southeast University, Nanjing, Jiangsu, People's Republic of China; 3Institute of Viruses and Infectious Diseases, Nanjing University, Nanjing, Jiangsu, People's Republic of China; 4Department of Infectious Diseases, Nanjing Drum Tower Hospital Clinical College of Nanjing Medical University, Nanjing, Jiangsu, People's Republic of China; 5Department of Infectious Diseases, Nanjing Drum Tower Hospital Clinical College of Nanjing University of Chinese Medicine, Nanjing, Jiangsu, People's Republic of China; 6Department of General Practice, Nanjing Second Hospital, Nanjing University of Chinese Medicine, Nanjing, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Chao Wu; Rui Huang, Department of Infectious Diseases, Nanjing Drum Tower Hospital, Affiliated Hospital of Medical School, Nanjing University, No. 321 Zhongshan Road, Nanjing, Jiangsu, 210008, People's Republic of China, Tel +86-25-83105890, Fax +86-25-83307115, Email dr.wu@nju.edu.cn; doctor_hr@126.comBackground: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging epidemic infectious disease with high mortality rate. This study aimed to investigate the association of red blood cell distribution width (RDW) and mortality risk in hospitalized SFTS patients.Methods: Clinical data of SFTS patients was retrospectively collected from three hospitals between October 2010 and August 2022. Cox proportional hazards model was used to identity the risk factors for fatal outcome. The predictive value of RDW for fatal outcome was evaluated by the receiver operating characteristic (ROC) analysis and Kaplan-Meier methods.Results: Of 292 patients, the median age was 61.5 years. Non-survivors showed higher RDW value than survivors (13.6% vs.13.0%, P < 0.001). The mortality rate was 44.8% in patients with elevated RDW compared to 18.4% of patients with normal RDW, with a relative risk (RR) of 2.439. Elevated RDW was an independent risk factor of mortality (hazards ratio: 1.167, P = 0.019). Patients with elevated RDW had a higher cumulative mortality than patients with normal RDW. The area under the ROC curve (AUC) of RDW for the prediction of mortality was 0.690 (P < 0.001).Conclusion: Elevated RDW was associated with higher mortality risk for patients hospitalized for SFTS. RDW may be helpful for risk stratification in SFTS patients.Keywords: severe fever with thrombocytopenia syndrome, red blood cell distribution width, prognosis, survival